My Havana : The Musical City of Carlos Varela - Arazoza, Ana Elena; Reloba, Xenia; Cumaná, María Caridad, 1964-; Dubinsky, Karen (Book collections on Project MUSE., 2014)
For more than thirty years, musician Carlos Varela has been a guide to the heart, soul, and sound of Havana. My Havana is a lyrical exploration of Varela's life and work, and of the vibrant musical, literary, and cinematic culture of his generation.